Activation of GPR119 Stimulates Human β-Cell Replication and Neogenesis in Humanized Mice with Functional Human Islets - Ansarullah; Colette Free; Jenica Christopherson; Quanhai Chen; Jie Gao; Chengyang Liu; Ali Naji; Alex Rabinovitch; Zhiguang Guo (Journal of Diabetes Research)
Using humanized mice with functional human islets, we investigated whether activating GPR119 by PSN632408, a small molecular agonist, can stimulate human β-cell regeneration in vivo. Human islets were transplanted under the left kidney capsule of immunodeficient mice with streptozotocin- (STZ-) induced diabetes. The recipient mice were treated with PSN632408 or vehicle and BrdU daily. Human islet graft function in the mice was evaluated by nonfasting glucose levels, oral glucose tolerance, and removal of the grafts. Immunostaining for insulin, glucagon, and BrdU or Ki67 was performed in islet grafts to evaluate α- and β-cell replication. Insulin and CK19 immunostaining was performed to evaluate β-cell neogenesis. Four weeks after human islet transplantation, 71% of PSN632408-treated mice achieved normoglycaemia compared with 24% of vehicle-treated mice. Also, oral glucose tolerance was significantly improved in the PSN632408-treated mice. PSN632408 treatment significantly increased both human α- and β-cell areas in islet grafts and stimulated α- and β-cell replication. In addition, β-cell neogenesis was induced from pancreatic duct cells in the islet grafts. Our results demonstrated that activation of GPR119 increases β-cell mass by stimulating human β-cell replication and neogenesis. Therefore, GPR119 activators may qualify as therapeutic agents to increase human β-cell mass in patients with diabetes.